Development of a Psychological Measurement: Synectic Thinking Style Scale for Indonesian Students - Achmad Syahid; Arung Samudera; Moh. Irvan; Rofiatul Hosna; Solicha (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2026)
Indonesia is a “space of imagination” rich in metaphorical and analogical traditions rich in symbols, allusions, and narratives, such as folktales, pantun, proverbs, wayang puppetry, and various forms of traditional Indonesian art. However, this space of imagination has not yet flowed into classrooms, thus stimulating students’ thinking styles. Furthermore, valid, reliable, and theory-based instruments are still very limited. Measuring synectic thinking styles that strive to create a creative, innovative, and globally competitive generation will only be policy rhetoric. This article aims to develop and validate a synectic thinking style measurement instrument designed to assess students’ engagement in metaphorical and creative thinking processes. This instrument is based on the synectic thinking style construct with two main theoretical dimensions by Gordon, making the strange familiar – which is understanding something unfamiliar through an existing knowledge framework – and making the familiar strange which is seeing something familiar from a new perspective. Data were collected online through a convenience sampling technique from 1,252 respondents, and after cleaning outliers, 607 responses were retained for analysis. Validity tests using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) showed a stable factor structure and met the goodness of fit criteria. The Rasch Model analysis supported high reliability and fulfilled the assumptions of local independence. Although several items were found to have similar content or sound, and the need for refinement of the distribution of item difficulty levels, this instrument was deemed suitable for use as an initial measurement of synectic thinking style as a result of a particular learning model. Further research is recommended for the development of adaptive and cross-context versions